Transanal endoscopic microsurgical submucosal dissection for recurrent rectal adenomas - Kouladouros, Konstantinos; Baral, Jörg (Digestive diseases, 2023)
Background: The local resection of recurrent rectal adenomas is a technically challenging task associated with increased local recurrence rate. Transanal endoscopic microsurgical submucosal dissection (TEM-ESD) uses traction to better expose the fibrotic submucosal layer, and therefore, is a valuable alternative for the treatment of such lesions. The aim of our study was to assess the feasibility and outcomes of TEM-ESD for the resection of recurrent rectal adenomas. Methods: We retrospectively analysed all TEM-ESD procedures performed in the Karlsruhe Municipal Hospital between 2012 and 2021 and isolated all cases of recurrent adenomas. Subsequently, we matched these cases 1:1 to TEM-ESD cases for primary rectal adenomas according to the size, localization, and histological type of the lesions and compared the outcomes between the two groups. Results: We identified 19 cases matching our criteria. The median diameter of the lesions was 25 mm and the median operating time 39 min. Macroscopic en bloc resection was achieved in 100% of the cases and histological complete en bloc resection in 78.9%. There was 1 case of conservatively treated postoperative bleeding. After a median follow-up period of 36 months, there was one local recurrence. After comparing those findings to the outcomes of TEM-ESD for primary rectal lesions, we found no significant differences on total operating time, complete en bloc resection rates, adverse events, and local recurrence. Conclusion: TEM-ESD is a feasible therapeutic option for the resection of recurrent rectal adenomas, offering short operating times as well as high en bloc resection and low recurrence rates.
Online veröffentlicht: 24. Februar 2022
Gesehen am 01.07.2024